Overexpression, crystallization and preliminary X‐ray characterization of Ruminococcus flavefaciens scaffoldin C cohesin in complex with a dockerin from an uncharacterized CBM‐containing protein. Issue 8 (1st August 2014) - Bule, Pedro; Ruimy‐Israeli, Vered; Cardoso, Vânia; Bayer, Edward A.; Fontes, Carlos M. G. A.; Najmudin, Shabir
<x xml:space="preserve">Abstract</x> Cellulosomes are massive cell‐bound multienzyme complexes tethered by macromolecular scaffolds that coordinate the efforts of many anaerobic bacteria to hydrolyze plant cell‐wall polysaccharides, which are a major untapped source of carbon and energy. Integration of cellulosomal components occurs via highly ordered protein–protein interactions between cohesin modules, located in the scaffold, and dockerin modules, found in the enzymes and other cellulosomal proteins. The proposed cellulosomal architecture for Ruminococcus flavefaciens strain FD‐1 consists of a major scaffoldin (ScaB) that acts as the backbone to which other components attach. It has nine cohesins and a dockerin with a fused X‐module that binds to the cohesin on ScaE, which in turn is covalently attached to the cell wall. The ScaA dockerin binds to ScaB cohesins allowing more carbohydrate‐active modules to be assembled. ScaC acts as an adaptor that binds to both ScaA and selected ScaB cohesins, thereby increasing the repertoire of dockerin‐bearing proteins that integrate into the complex. In previous studies, a screen for novel cohesin–dockerin complexes was performed which led to the identification of a total of 58 probable cohesin–dockerin pairs. Four were selected for subsequent structural and biochemical characterization based on the quality of their expression and the diversity in their specificities. One of these is C12D22, which comprises the cohesin from the adaptor ScaC protein bound to the dockerin of a CBM‐containing protein. This complex has been purified and crystallized, and data were collected to resolutions of 2.5 Å (hexagonal, P65), 2.16 Å (orthorhombic, P212121) and 2.4 Å (orthorhombic, P21212) from three different crystalline forms.